2007
DOI: 10.1007/s00330-007-0776-x
|View full text |Cite
|
Sign up to set email alerts
|

Height gain of vertebral bodies and stabilization of vertebral geometry over one year after vertebroplasty of osteoporotic vertebral fractures

Abstract: The height gain of vertebral bodies after vertebroplasty and geometrical stability was evaluated over a one-year period. Osteoporotic fractures were treated with vertebroplasty. The vertebral geometry and disc spaces were analysed using reformatted computed tomography (CT) images: heights of the anterior, posterior, and lateral vertebral walls, disc spaces, endplate angles, and minimal endplate distances. Vertebrae were assigned to group I [severe compression (anterior height/posterior height) <0.75] and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…(16,31) Such leaks might occur through fractured endplates or vacuum clefts or may result from iatrogenic endplate perforations with the needle tip. (32) The hard cement into the disk probably alters the load transfer increasing the mechanical pressure of the endplate of the adjacent vertebral body, increasing the risk of a VF in osteoporotic vertebrae. (33) In addition, the asymmetrical distribution of the cement contributes to the alteration in the biomechanics of the vertebra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16,31) Such leaks might occur through fractured endplates or vacuum clefts or may result from iatrogenic endplate perforations with the needle tip. (32) The hard cement into the disk probably alters the load transfer increasing the mechanical pressure of the endplate of the adjacent vertebral body, increasing the risk of a VF in osteoporotic vertebrae. (33) In addition, the asymmetrical distribution of the cement contributes to the alteration in the biomechanics of the vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…Cement leakage into the disk has been previously associated with adjacent VF after VP . Such leaks might occur through fractured endplates or vacuum clefts or may result from iatrogenic endplate perforations with the needle tip . The hard cement into the disk probably alters the load transfer increasing the mechanical pressure of the endplate of the adjacent vertebral body, increasing the risk of a VF in osteoporotic vertebrae .…”
Section: Discussionmentioning
confidence: 99%
“…It is intuitive that this could prevent or treat kyphosis, avoid gastrointestinal complications associated with spinal deformity, and maintain pulmonary function. Although improvement in kyphosis has been reported [ 42 ], the longterm clinical benefi ts of vertebral height restoration have not been clearly demonstrated, and vertebroplasty, as well as kyphoplasty, has now been shown to restore lost vertebral height in some patients [ 43 ]. McKiernan et al [ 44 ] demonstrated "dynamic mobility" (positional changes in the height of fractured vertebral bodies) in 44% of 41 consecutive patients undergoing vertebroplasty, as well as some restoration of lost vertebral height in these patients.…”
Section: Height Restorationmentioning
confidence: 97%
“…Vertebral augmentation is a common treatment for restoring the geometry and mechanical competence of vertebrae affected by severe osteoporosis [1][2][3][4][5] or metastatic involvement [6][7][8][9][10]. Vertebroplasty technology is developing rapidly, with one facet of the new technology focused on developing new protocols that restore the vertebra to its pre-disease stiffness [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%